Analisis Dampak Penerapan Teknologi Informasi dan Komunikasi (TIK) Dalam Pengembangan Pembelajaran Kemampuan Dasar Matematika Berstandar National Council Of Teacher Of Mathematics (NCTM) - Junaedi, Lukman; Arif, Muchamad (Universitas Narotama, 2024)
The application of Information and Communication Technology (ICT) in the development of elementary mathematics learning has a significant impact on the learning process. This study aims to analyze how ICT can improve the teaching of basic mathematics skills based on the National Council of Teachers of Mathematics (NCTM) standards. The main focus of this study is to explore the influence of ICT on the understanding of basic mathematical concepts, as well as students' critical thinking and problem-solving skills. The analysis was carried out by examining various methods of using ICT that are in line with the principles and standards set by NCTM. The results of the study are expected to provide new insights for the development of more effective curricula and learning strategies. By using ICT, it is hoped that students can more easily understand mathematics materials, develop communication skills, and improve overall learning outcomes. In addition, this study will also look at the challenges faced in the implementation of ICT and how solutions can be adopted to optimize its application in mathematics learning. Keywords: Mathematics, ICT, NCTM